A pilot study on the contents of selected pollutants in fish from the Tiber River (Rome) - Mancini, L; Caimi, S; Ciardullo, S; Zeiner, M; Bottoni, P; Cautadella, S; Caroli, S.; TANCIONI, LORENZO (Microchemical Journal, 2005)
In the framework of a project aimed at the study of the catchment basin of the Tiber River (Latium Region, Italy), a pilot survey was conducted in order to assess the presence of selected toxic trace elements, namely As, Cd, Hg and Pb, in muscle tissues of fish caught in different tracts of Tiber River (urban area of Rome and different rural areas upstream and downstream). The analysed species were Leuciscus cephalus (Ciprinidae) and Anguilla anguilla (Anguillidae). Determinations were carried out by means of Sector Field Inductively Coupled Plasma Mass Spectrometry (SF-ICP-MS). Preliminary data (ranges of concentration in mug g(-1), freeze-dried mass: As, 0.73-3.62; Cd, 0.0002-0.001; Hg, 0.18-0.31; Pb, 0.02-0.09) revealed no significant differences among the sets of results relevant to the various sampling stations. The total content of each element seems to be related with a general condition of low-level pollution of the area under study. (C) 2004 Elsevier B.V. All rights reserved.